Putting the Just-In-Time Philosophy into Practice
IX, 129 p.
Keywords: This book describes both the essential features of Just-In-Time (JIT) how JIT can be successfully approaches to manufacturing and implemented. JIT marks a significant departure from previous western approaches to manufacturing management, and aims to improve quality levels and customer service while decreasing lead times and inventory levels. The use of simple though effective methods can, with proper management, lead to continual improvements in the manufacturing operation. A number of companies have now implemented JIT and some of these implementations have been very successful. However, what is becoming increasingly clear is that there is a significant number of JIT implementations that fail to achieve the potential benefits of JIT. It is not an easy task, and there are a number of pitfalls that await the unwary manager. My motivation for writing this book has been my experience of working with companies that have been successful in JIT and of seeing what needs to be done and how the implementing most common pitfalls can be avoided. The book is oriented towards batch manufacturing since this accounts for a large proportion of manufacturing in most western countries. Other types (including process, mass and jobbing) can also profitably use many of the JIT techniques to improve their operation.